Association of rs4646903 and rs1048943 CYP1A1 estrogen-metabolizing gene polymorphisms with estrogen receptor-positive breast cancer in Kenyan women - Murithi, Mary; Nyanjom, Steven; Mobegi, Victor; Shahin, Sayed; Makokha, Francis (Archives of Biological Sciences, 2023)
Paper description: The rs4646903 and rs1048943 polymorphisms in CYP1A1 estrogen metabolizing gene have shown associations with breast cancer in some populations. A causal-comparative research design was used. Genotyping of the target single-nucleotide polymorphisms was performed using polymerase chain reaction restriction fragment length polymorphism. The variant genotypes CC of rs4646903 and AG and GG of rs1048943 showed significant association with estrogen receptor-positive breast cancer in Kenyan women. Different populations with the same polymorphisms exhibit differences in breast cancer risk. Findings from this study inform on the polymorphisms relevant for risk assessment of breast cancer in Kenyan women. Abstract: Breast cancer is the most prevalent neoplasm and the second leading cause of death among females in Kenya. Estrogen and its metabolites are known risk factors for breast cancer. Polymorphisms in these genes and breast cancer susceptibility are unique among different populations. This study aimed to determine the probable associations between estrogen-metabolizing gene variations and other risk factors for breast cancer risk in Kenyan women. Buffy coat samples were obtained from patients diagnosed with estrogen receptor-positive breast cancer, benign breast disease, and healthy volunteers. Genotyping of target polymorphisms was conducted using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) analysis. The rs4646903 variant genotype CC was associated with breast cancer in the case-control model (P=0.001); the heterozygous genotype TC (P=0.01) and the luminal B molecular subtype (P=0.02) showed increased odds of late-stage breast cancer. The rs1048943 variant genotype GG was associated with breast cancer in the case-benign model (P=0.04), whereas CG was associated with breast cancer in the case-control model (P=0.02). These findings imply that the rs4646903 and rs1048943 variant genotypes are involved in breast cancer risk in Kenyan women. Hence, they may be explored further as potential markers for the disease.